As shown in the figure above, a circle is inscribed in quadrilateral A B C D , where M and N are midpoints of A C and B D , respectively, A B = 5 , C D = 9 and A C 2 + B D 2 + 4 M N 2 = 2 1 8 .
Find the value of B C × D A .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
You have shown that if such a configuration exists, the answer is 42. Does such a configuration exist?
@Calvin Lin Uhm, if you won't mind, this problem is more related to Apollonius' theorem than just problem solving on triangle. Can you change the relevant wiki, please? Sorry to bother you.
L
e
t
a
=
A
B
,
b
=
B
C
,
c
=
C
D
,
d
=
D
A
;
p
=
A
C
,
q
=
B
D
;
x
=
M
N
.
P
i
t
o
t
T
h
e
o
r
e
m
:
−
a
+
c
=
b
+
d
.
⟹
(
b
2
+
2
b
d
+
d
2
)
=
(
a
+
c
)
2
=
1
9
6
.
E
u
l
e
r
′
s
M
i
d
p
o
i
n
t
T
h
e
o
r
e
m
:
−
a
2
+
b
2
+
c
2
+
d
2
=
p
2
+
q
2
+
4
x
2
=
2
1
8
.
⟹
b
2
+
d
2
=
2
1
8
−
5
2
−
9
2
=
1
1
2
.
∴
1
9
6
=
b
2
+
2
b
d
+
d
2
=
(
b
2
+
d
2
+
2
b
d
)
=
1
1
2
+
2
b
d
.
∴
B
C
∗
D
A
=
b
d
=
2
1
∗
(
1
9
6
−
1
1
2
)
=
4
2
.
The author Mr. H.M. 유 has already shown the existence of such a quadrilateral.
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Apollonius's Theorem
This solution uses Apollonius' Theorem .
Use it on △ A B D , △ B C D , and △ A C D respectively.
A B 2 + A D 2 = 2 ( A N 2 + B N 2 ) ⋯ A
B C 2 + C D 2 = 2 ( C N 2 + B N 2 ) ⋯ B
A N 2 + C N 2 = 2 ( M N 2 + A M 2 ) ⋯ C
Calculate A + B + 2 × C .
A B 2 + B C 2 + C D 2 + D A 2 = 4 A M 2 + 4 B N 2 + 4 M N 2 = A C 2 + B D 2 + 4 M N 2
Therefore, B C 2 + D A 2 = 1 1 2 .
From the question, we know that B C + D A = 1 4 .
∴ B C ⋅ D A = 4 2 .
Now let's prove that this configuration of points actually exists.
From the information above, we can safely say that B C = 7 − 7 and D A = 7 + 7 .
Since we only need to prove that at least one configuration exists, I'm going to prove only one.
Consider ∠ B C D = 2 π .
Then let O , P , Q be the center of the circle, and the points where B C , C D contact with the circle, respectively.
We're going to draw a tangent line B X and D Y from point B and point D , such that B X = 5 and D Y = 7 + 7 .
r is the radius of the circle, and then let's just say 0 < 2 < r < 4 < 7 − 7 , to make this easier.
B X , C Y meets with the circle at points R and S respectively.
Then note that C P = C Q = r .
From it we can see that B P = 7 − 7 − r , X R = − 2 + 7 + r , D Q = 9 − r , Y S = − 2 + 7 + r .
Oh. Seems like X R = Y S . Then ∠ X O R = ∠ Y O S .
Then let's just say ∠ P O C = α , ∠ B O R = β , ∠ Y O S = γ , ∠ D O Q = δ .
Since we already know O X = O Y , for X and Y to become an identical point, we need α + β + γ + δ = π .
Then, tan ( α + δ ) = − tan ( β + γ ) .
tan α = r r , tan β = r 7 − 7 − r , tan γ = r − 2 + 7 + r , tan δ = r 9 − r .
tan ( α + δ ) + tan ( β + γ ) = 1 − r 9 − r r r + r 9 − r + 1 − r 2 ( 7 − 7 − r ) ( − 2 + 7 + r ) r 7 − 7 − r + r − 2 + 7 + r = 2 r − 9 9 + 2 r 2 − ( 9 − 2 7 ) r + ( 2 1 − 9 7 ) 5 r = 0
Then 1 0 r 2 − 4 5 r + 1 8 r 2 − 9 ( 9 − 2 7 ) r + 9 ( 2 1 − 9 7 ) = 0 .
Let f ( r ) = 2 8 r 2 − 4 5 r − 9 ( 9 − 2 7 ) r + 9 ( 2 1 − 9 7 ) .
f ( 2 ) f ( 4 ) = 2 2 − 9 ( 1 8 − 4 7 + 2 1 − 9 7 ) < 2 2 − 9 ( 3 9 − 3 5 ) = 2 2 − 3 6 < 0 = 2 6 8 − 9 ( 3 6 − 8 7 + 2 1 − 9 7 ) > 2 6 8 − 9 ( 5 7 − 4 4 ) = 1 5 1 > 0
Therefore f ( r ) = 0 has a solution where 2 < r < 4 , and therefore, the configuration of points A , B , C , D exists such that it would satisfy the given condition.
Formula: (Euler's midpoint theorem)
A B 2 + B C 2 + C D 2 + D A 2 = A C 2 + B D 2 + 4 M N 2